Aktivitas Antioksidan Jus Tomat pada Pencegahan Kerusakan Jaringan Paru-Paru Mencit yang Dipapar Asap Rokok (Genetic Diversity of Banana with B Genom Using Microsatelite Marker) - Aditya Marianti (Biosaintifika: Journal of Biology & Biology Education)
<!-- p { margin-bottom: 0.08in; } --> The activities of tomato juice’s antioxidant for the prevention of lung tissues damage in mice cigarette smoke induces endogen antioxidant is no longer effective on oxidative stress control towards cigarette consumer lung, thus exogenous antioxidant is a must. A kind of exogenous antioxidant is lycopen, a content of tomato. 40 mice is divided into 5 groups with 8 of each. Group I is the controlling group, group II is the negative control, and group III, IV, V are the group of mice that is supplied by tomato juice on the 1,7 g/100 g weight/day ; 3,4 g/100 g weight/day; and 5,1 g/100 g weight/day dozes. Each group, except the control one, is forced by cigarette smoke for 15 minutes per day in 54 days. On the 55th day, all mice is sacrificed. Specimens of their lungs are made in the way of histological by haematoxylin – eosin method. The data is about the comparison of lung tissue failed on each group, that is analyzed by Anava. The observation of each tissue on the group II showed emfisema pattern, that is alveolus membrane epithelia cell with no nucleus nor endothelium, with wide alveolus lumen and loose alveolus junction. The identical situation also found on group III. The failed tissue cannot be found on group IV and V. Antioxidant of tomato is capable of controlling lung tissue failed of mice of cigarette smoke. Keywords. Tomato juice, antioxidant, cigarette smoke, lung tissues